Synthesis and reactivity of N@C60O. - Jones, M; Britz, D; Morton, J; Khlobystov, A; Porfyrakis, K; Ardavan, A; Briggs, G (2006)
The endohedral fullerene epoxide N@C60O was synthesised, isolated by High Performance Liquid Chromatography (HPLC), and characterised by Electron Spin Resonance (ESR). This nitrogen radical displays predominantly axial symmetry characteristics as expected for a monoadduct, evidenced by a zero-field splitting D parameter of 6.6 MHz and an E parameter of 0.5 MHz in powder at 77 K. Photo- and thermally-activated silencing of the nitrogen radical were observed, the latter showing the evolution of a new spin signal during heating at 100 degrees C. We suggest that loss of nitrogen spin is due to coupling with a radical formed by opening of the epoxide ring. This implies that the reaction of C60O with C60 in the solid state proceeds via a radical, rather than ionic, intermediate.